Research on Criminal Regulation of Internet Violence Behavior - Qi Liu; Zihan Wang (Studies in Law and Justice, 2023)
In the contemporary society, “violence” is no longer a simple physical injury, with the continuous development of Internet technology, the phenomenon of network violence is becoming more and more intense. For example, netizens encouraged “cat or cat” to commit suicide by drinking pesticide live broadcast, and malicious network blasting caused teachers’ heart attack to tragedy, such as “rice circle human flesh search”, abusive war and so on. These events are different from the physical harm behavior in the real world, but they also fully expose the serious social harm of network violence. Therefore, so as to valid combat online violence, it is necessary to improve the legal system and fully leverage the role of criminal law and legal norms. In order to promote the maturity of the criminal law system of network violence, this paper will discuss the legitimacy of the criminal system of network violence, so as to promote the maturity of the legal system of network violence.